2005
DOI: 10.1093/jurban/jti049
|View full text |Cite
|
Sign up to set email alerts
|

Illicit Opioid Use in Canada: Comparing Social, Health, and Drug Use Characteristics of Untreated Users in Five Cities (OPICAN Study)

Abstract: Most of the estimated 125,000 injection drug users (IDUs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
118
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(126 citation statements)
references
References 63 publications
4
118
1
3
Order By: Relevance
“…It has been previously reported that there is a higher proportion of injection equipment sharing and overdoses in Montreal compared to Vancouver. 8,51 Broad implementation of harm reduction measures such as a decentralized needle exchange and a supervised injection facility in Vancouver may contribute to lower levels of risky injection practices. On the other hand, Montreal participants have received more psychological treatment than Vancouver and have been on MMT more times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that there is a higher proportion of injection equipment sharing and overdoses in Montreal compared to Vancouver. 8,51 Broad implementation of harm reduction measures such as a decentralized needle exchange and a supervised injection facility in Vancouver may contribute to lower levels of risky injection practices. On the other hand, Montreal participants have received more psychological treatment than Vancouver and have been on MMT more times.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Institutional sources estimate approximately 80,000 regular opioid users in Canada 6 with geographic differences in prevalence and trends. Although the "street" availability of prescription analgesic opioids such as hydromorphone and morphine has increased in recent years, 7,8 intravenous use of heroin prevails in Vancouver and Montreal. 5,[9][10][11] Injectors are exposed to life-threatening health risks such as drug overdoses, bloodborne viral infections, endocarditis, and others.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] The proportion of drug users who smoke crack cocaine and are homeless or have marginal housing has recently been reported to be as high as 86.6% in Vancouver, 66.7% in Edmonton and 62.4% in Toronto. 8 In the United States, a seminal cross-sectional study involving inner-city young adults showed that smoking of crack cocaine was associated with HIV infection. 9 However, in Canada, despite the documentation of changing patterns of drug use in many communities, 8 little is known about the impact that increased smoking of crack cocaine has had on the HIV epidemic.…”
mentioning
confidence: 99%
“…As also shown elsewhere, cocaine injection in a large number of instances occurs in combination with other drugs (typically opioids, i. e., so-called injected »speed-ball«; Fischer et al, 2005a). The vast majority (87.2 %) of those who also used crack used the drug by inhaled (smoked) route of administration.…”
Section: S P E C I a L I S S U Ementioning
confidence: 73%